Litopenaeus Vannamei Shrimp Pond Water Temperature And PH Monitoring System Using IoT-Based Sugeno Fuzzy Method - Sita Kirana Atikah; Rahmat Kurniawan R; Muhammad Siddik Hasibuan (SEAN Institute, 2023)
In order to make it easier for white shrimp (Litopenaeus vannamei) farmers to monitor pond water quality so as not to disrupt the growth process of white shrimp, a system was built that can be used to monitor and control pH and water temperature conditions remotely using pH sensors and temperature sensors based on IoT. Internet of Things or IoT is a technology that uses the internet to carry out a process of sending data to several devices without using the help of computers and humans. In this case the research was carried out using two water quality parameters, namely water temperature and pH level. This control uses two actuators, namely a water wheel which is useful for lowering the water temperature and a water pump for adding water with the aim of increasing or decreasing the pH level using the fuzzy Sugeno method. The results of the error presentation on the pH sensor were 0.002% and the precision behavior (accuracy) on the pH sensor circuit was 99.998%, the error presentation results on the temperature sensor were 0.038% and the precision behavior (accuracy) on the temperature sensor circuit was 99.962%. carried out by researchers, it can be concluded that the fuzzy sugeno method can fulfill the purpose of monitoring the pH and water temperature of Litopenaeus vannamei shrimp pond water based on IoT, by using 3 temperature rules, namely low temperature: 0-26, normal temperature: 27-30, high temperature: 31 - 45 and 3 rule pH, namely acid: 0 -7.4, normal: 7.5-8.5, alkaline: 8.6 – 14.